CONTROLLING IN METALLURGICAL PRODUCTION OF RUP «BMZ» - V. M. Machulin; V. E. Sidorchuk; S. N. Astratov (Литьë и металлургия)
Controlling is one of the most effective management instruments at the modern stage of market relations.